Aptamer-functionalized targeted siRNA delivery system for tumor immunotherapy. (1st March 2022) - Lv, Haiyin; Wang, Tengfei; Ma, Fanshu; Zhang, Kunchi; Gao, Tian; Pei, Renjun; Zhang, Ye
Abstract: Programmed death ligand 1 (PD-L1) overexpressed on the surface of tumor cells is one of the reasons for tumor immune escape. Reducing PD-L1 expression has been proved to be an effective strategy to facilitate immune system activation and inhibit tumor progression. RNA interference (RNAi) is a promising technology for gene regulation in tumor therapy. In this study, we constructed a targeted siRNA delivery system NPs@apt to transfect PD-L1 siRNA into human non-small-cell lung carcinoma cell line (A549) for inhibiting tumor immune evasion. NPs@apt was prepared by compressing PD-L1 siRNA with cationic Lipofectamine 2000, fusing with erythrocyte membrane-derived nanovesicles, and further modifying with targeting AS1411 aptamer. The introduction of erythrocyte membrane endowed the siRNA delivery system with lower cytotoxicity and the ability to escape from the phagocytosis of macrophages. The stability of NPs@apt and the protection to loaded siRNA were confirmed. In vitro studies after NPs@apt treatment demonstrated that PD-L1 siRNA was selectively delivered into A549 cells, and further resulted in PD-L1 gene knockdown, T cell activation and tumor cell growth inhibition. This study offered an alternative strategy for specific siRNA transfection for improving anti-tumor immunity.